2014
DOI: 10.1016/b978-0-12-800977-2.00003-6
|View full text |Cite
|
Sign up to set email alerts
|

Histone-Mediated Epigenetics in Addiction

Abstract: Many of the brain regions, neurotransmitter systems, and behavioral changes that occur after occasional drug use in healthy subjects and after chronic drug abuse in addicted patients are well characterized. An emerging literature suggests that epigenetic processes, those processes that regulate the accessibility of DNA to regulatory proteins within the nucleus, are keys to how addiction develops and how it may be treated. Investigations of the regulation of chromatin, the organizational system of DNA, by histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 146 publications
(189 reference statements)
0
13
0
Order By: Relevance
“…Recent finding also suggest that palatable food self-administration during abstinence, as a means of maintaining voluntary abstinence, may also block the development of the incubation of heroin, but not methamphetamine seeking (Venniro et al 2016). The results from these studies have also revealed a number of potential targets for preventing drug relapse such as orexin receptors (Schmeichel et al 2015), brain-derived neurotrophic factor (Koskela et al 2017), dopamine D3 receptors (Sokoloff and Le Foll 2017), metabotropic glutamate receptors (Pomierny-Chamioło et al 2014), and pathways involved in epigenetic regulation and synaptic plasticity (Hitchcock and Lattal 2014; Wolf 2016).…”
Section: Enhanced Drug-seeking/relapse Vulnerabilitymentioning
confidence: 99%
“…Recent finding also suggest that palatable food self-administration during abstinence, as a means of maintaining voluntary abstinence, may also block the development of the incubation of heroin, but not methamphetamine seeking (Venniro et al 2016). The results from these studies have also revealed a number of potential targets for preventing drug relapse such as orexin receptors (Schmeichel et al 2015), brain-derived neurotrophic factor (Koskela et al 2017), dopamine D3 receptors (Sokoloff and Le Foll 2017), metabotropic glutamate receptors (Pomierny-Chamioło et al 2014), and pathways involved in epigenetic regulation and synaptic plasticity (Hitchcock and Lattal 2014; Wolf 2016).…”
Section: Enhanced Drug-seeking/relapse Vulnerabilitymentioning
confidence: 99%
“…Recent attention has focused on epigenetic mechanisms that modulate interactions between DNA, histones, and other aspects of chromatin structure (Hitchcock and Lattal, 2014). Many studies have now documented enhancements in memory caused by administration of drugs that inhibit histone deacetylases (HDACs), which prevent the removal of acetyl groups from specific amino acid sites of histones(e.g., Dagnas et al 2015; Foley et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Broadly, epigenetics refers to changes in chromatin structure that influence gene expression without affecting gene sequence (Kwapis & Wood ; Levenson & Sweatt ). Two primary mechanisms of epigenetic regulation are through direct DNA methylation and histone modification, and these mechanisms allow for the integration and storage of information in species ranging from yeast and plants up to humans (reviewed in Hitchcock & Lattal ; Vanyushin ). Chromatin refers to the complex of DNA and proteins that reside in the nucleus of a cell, and the primary proteins that comprise chromatin are histones.…”
Section: The Need For a Molecular Approach: Epigenetic Mechanisms In mentioning
confidence: 99%